Nsp1 stalls DNA polymerase α at DNA hairpins - Andrey G. Baranovskiy; Lucia M. Morstadt; Nigar D. Babayeva; Tahir H. Tahirov (Scientific Reports)
Abstract The human primosome, a four-subunit complex of DNA primase and DNA polymerase alpha (Polα), plays a critical role in DNA replication by initiating RNA and DNA synthesis on both chromosome strands. A recent study has shown that a major virulence factor in the SARS-CoV-2 infection, Nsp1 (non-structural protein 1), forms a stable complex with Polα but does not affect primosome activity. Here we show that Nsp1 inhibits DNA synthesis across inverted repeats prone to hairpin formation. Analysis of current structural data revealed the overlapping binding sites for Nsp1 and the winged helix-turn-helix domain of RPA (wHTH) on Polα, pointing to a potential competition between them. Comparison of the inhibitory effect of Nsp1 and wHTH on DNA hairpin bypass by Polα showed an eightfold lower IC50 value for Nsp1 (1 µM). This study provides valuable insight into the mechanism of inhibition of human DNA replication by Nsp1 during a SARS-CoV-2 infection.